A Flexible Patch-Type Strain Sensor Based on Polyaniline for Continuous Monitoring of Pulse Waves - Kang, Sehong; Rachim, Vega Pradana; Baek, Jin-Hyeok; Lee, Seung Yong; Park, Sung-Min (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
A flexible, patch-type strain sensor is described for continuous monitoring of pulse waves. The proposed sensor exploits the piezo-resistivity of the conductive polymer, polyaniline (PANI), to detect dynamic volume changes in blood vessels owing to pulse waves. The proposed PANI film was fabricated through electrodeposition, which is considered as a suitable low-cost technique for mass production in the sensor manufacturing industry. Thus, it is prospective for a disposable wearable sensing system solution in remote healthcare applications. Besides, a flexible sensor packaging can be achieved by laminating the PANI films and an ECOFLEX elastomer to the film bandage. The proposed PANI sensor has high sensitivity (gauge factor of 74.28) and linearity (R-2 = 0.99). It also showed a high correlation with commercially available photoplethysmography (PPG) sensor with the small bias and confidence interval to the PPG sensor: bias < 0.1% and confidence interval < 3% for all subjects. Moreover, the proposed PANI sensor was tested for prospective circulatory system-related applications such as measuring heart rate, stiffness index, and pulse transit time. Finally, the proposed study suggests that the proposed PANI sensor is a promising candidate for continuous, long-term, unobtrusive pulse wave monitoring, which can provide real-time insights into an individual's health status.
Keywords: ARTERIAL STIFFNESS; TRANSIT-TIME; PRESSURE; COMPOSITE; FORM